The Influence of Internal Control and E-Budgeting on the Performance of Local Government Agencies Through the Implementation of Good Governance - Sakti, RTS Resa Anggia; Afiah, Nunuy Nur; Mulyani, Sri Mulyani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
One of the refocusing of the budget that occurred in 2020 is the focus on the Health Sector. However, the low absorption of the budget and the failure to achieve performance targets in the health sector indicate that there are problems related to government performance which should be managed economically, efficiently, and effectively. The purpose of this study was to determine the direct and indirect influence of the government's internal control system and the implementation of e-budgeting on the performance of local government agencies in the health sector through the implementation of good government governance. The study used a quantitative descriptive verification method with a sample of 28 Governments in West Java. Data analysis technique using SEM-PLS. The results show that SPIP has a direct or indirect effect on performance through the implementation of good government governance, SPIP has no effect on performance and implementation of GGG through the implementation of e-budgeting, implementation of e-budgeting has a direct effect on GGG, e-budgeting implementation has no effect on performance, SPIP has no effect on the implementation of e-budgeting, the implementation of GGG has an effect on performance, the implementation of e-budgeting has an indirect effect on performance through good government governance.